Transcending Translation: Using the Potential of Emojis in Reading Comprehension for Young ESL Learners - Maleeha Nazim; Dr. Zahra Nazim; Mehak Muneer (Indus Journal of Social Sciences, 2025)
The present research focused on teaching reading comprehension to students of elementary level through emoji to avoid translation also, exploring the effect of emoji on students in learning of English as a second language. The sample for the current study consisted of 50 students of grade 6 and 3 English teachers from a private school in Lahore, Pakistan. Mixed method research was used for this study. The data was collected through experimental research which was based on a checklist using a Likert scale to observe students' reading comprehension also, a pilot study was conducted to check the validity of the checklist. The data was analyzed with the help of SPSS statistical software for calculating the Pearson correlation. To add a qualitative dimension to the study, structured interviews were conducted to explore teachers' attitudes towards emoji teaching. The results have identified that teaching with emoji brought a significant difference in students’ performance and helped them reduce their problems, which they had in understanding comprehension passages without any help. Based on the findings the present research recommended that the future studies can increase the sample size, for more accurate evidence and generalizing the results respectively.